2015
DOI: 10.1007/s40037-015-0219-3
|View full text |Cite
|
Sign up to set email alerts
|

How educational innovations and attention to competencies in postgraduate medical education relate to preparedness for practice: the key role of the learning environment

Abstract: IntroductionMany training programmes in postgraduate medical education (PGME) have introduced competency frameworks, but the effects of this change on preparedness for practice are unknown. Therefore, we explored how elements of competency-based programmes in PGME (educational innovations, attention to competencies and learning environment) were related to perceived preparedness for practice among new consultants.MethodsA questionnaire was distributed among 330 new consultants. Respondents rated how well their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…The impact of such changes on day to day learning and supervision has been questioned [ 59 , 61 ]. Dijkstra et al [ 13 ] found the influence of structural changes on trainees’ learning was mediated by ‘on the ground’ features of the clinical learning environment. It has been suggested that local approaches to cultural change may be effective [ 59 , 62 ] in improving clinical learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of such changes on day to day learning and supervision has been questioned [ 59 , 61 ]. Dijkstra et al [ 13 ] found the influence of structural changes on trainees’ learning was mediated by ‘on the ground’ features of the clinical learning environment. It has been suggested that local approaches to cultural change may be effective [ 59 , 62 ] in improving clinical learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…The way people in a particular department approach the process of learning is considered a reflection of the learning environment [ 19 ]. This learning environment is thought to play a key role in the development of residents towards independent practice [ 20 ]. It has been hypothesized that the learning environment could be an important driver of burnout [ 6 , 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…When it concerns resident doctors, this working environment resembles the learning environment [ 11 ], which is a construct that includes formal and informal aspects of the training program, organizational aspects within the teaching hospital [ 12 ] as well as the overall atmosphere [ 13 ]. The learning environment is thought to play a key role in the development of residents towards independent practice [ 14 ] and it has been postulated to be an important contributor to burnout [ 2 ]. A previous content analysis of instruments that assess the learning environment showed that the majority of the items of these instruments relate to a theoretical framework that characterizes the learning environment in three broad domains: the content of the program, the interpersonal aspects and atmosphere of the program, and the structure and organization of the program [ 15 ].…”
Section: Introductionmentioning
confidence: 99%